Divergent Patterns of Carbon, Nitrogen, and Phosphorus Mobilization in Forest Soils - Brödlin, Dominik; Kaiser, Klaus; Hagedorn, Frank (Frontiers in Forests and Global Change, 2019)
Carbon (C), nitrogen (N), and phosphorus (P) become released in inorganic or organic forms during decomposition of soil organic matter (SOM). Environmental perturbations, such as drying and rewetting, alter the cycling of C, N, and P. Our study aimed at identifying the patterns and controls of C, N, and P release in soils under beech forests. We exposed organic and mineral horizons from a nutrient availability gradient in Germany to permanent moist conditions or dry spells in microcosms and quantified releases of inorganic and organic C, N, and P. Under moist conditions, mobilization of DOC, DON, and DOP were interrelated and depended on the C:N:P ratio of SOM, whilst net mineralization rates of C, N, and P correlated poorly. Mineralization of C decreased with soil depth from Oi to A horizons, reflecting the increasing SOM stability. Net mineralization of N and P showed divergent depth patterns. In the Oi horizon, net mineralization was smaller for N than for C and P, indicating more pronounced microbial immobilization for N than for P. In A horizons, net mineralization of P was less than of N, very likely because of strong sorption of released phosphate by mineral phases. Counterintuitively, net P mineralization in A horizons increased toward P-poor sites, probably due to decreasing contents of clay and pedogenic oxides, and thus, declining P sorption. Drying and rewetting caused stronger release of inorganic and organic P, and organic N than of inorganic C and inorganic N, most likely by lysis of microbial biomass with tight C:N:P ratios. Due to the divergent patterns in N and P cycling, the organic layer seems more crucial for net mineralization of P than the mineral soil; for N the mineral soil appears more important. Consequently, the loss of the organic layer would deteriorate P nutrition, in particular at nutrient-poor sites. Overall, our results indicate that the cycling of C, N, and P in soil is not directly coupled because of the different microbial immobilization and, in the mineral soil, differential sorption of inorganic N and P. This may ultimately cause imbalances in N and P nutrition of forests.